ผลของลิเทียมอะลูมิเนตต่อการเผาผนึกเซรามิกแมกนีเซียมอะลูมิเนตสปิเนล - เอกรินทร์ สุบุญ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this work, effects of Li5AlO4 addition on sinterability of MgAl2O4 spinel were investigated. Two-difference MgAl2O4 spinel powders (S30CR and TSP-15) were homogeneously added into an aquatic solutions of Li5AlO4. The concentration of Li5AlO4 focused in this work were fix at 0, 1, 5 and 10 wt%. Green samples were pressed into pellet under 50 MPa . Then sintered by different process. Such as sintering in air at 1100-1600oC, hot-pressing at 1600-1700oC and sintering in air at 1600oC following by hot-isostatic pressing at 1500oC for 2 h under 200 MPa. The results showed the obtained green samples were sintered in air at 1600oC for 2 h had fine grain with high relative density over 98%. Using 1wt% of Li5AlO4 additions increased grain size and relative density of both samples. At 1600oC had similar reletivedensity. S30CR sample turned into translucent by Hot-pressed process at 1700oC under 40 MPa. On the other hand, TSP-15 sample still opague. Sintered in air following by hot-isostatic pressed with Li5AlO4 doped highly increased grain size of both samples up to 54.81-60.26 micron. There was no improvement founded in hot-isostatic pressed process. Both samples still milky white and had nearly grain size about 4-6 micron. The light transmittance of both S30CR and TSP-15 sintered samples were low because of light scattering.